Using technology-based vocabulary instruction inside and outside of the classroom - Alahmadi, Alaa; Albaqami, Saad Eid; Foltz, Anouschka (Frontiers in Communication, 2023)
The current pre-test post-test study explored the use of WhatsApp for vocabulary acquisition inside and outside the English as a Foreign Language classroom. Native Arabic undergraduate students learned English vocabulary items both inside and outside of the classroom using WhatsApp groups. Pre- and post-tests gauged participants knowledge of the vocabulary items used in the intervention as well as control items. An additional questionnaire explored participants’ satisfaction with using WhatsApp inside and outside of the classroom. We found a small, but significant, vocabulary learning effect for using WhatsApp outside of the classroom, but no such effect for the use of WhatsApp inside the classroom. The questionnaire results additionally showed that students were highly satisfied with the use of WhatsApp to learn vocabulary, especially in terms of instructor availability. Finally, we found that students who were more motivated to use WhatsApp inside the classroom showed higher learning gains inside the classroom than those less motivated. We discuss the results with respect to the role of space and motivation for vocabulary acquisition using technologies such as WhatsApp.